Intralymphatic immunotherapy of pollen-induced rhinoconjunctivitis: a double-blind placebo-controlled trial. Issue 1 (December 2016) - Hylander, Terese; Larsson, Olivia; Petersson-Westin, Ulla; Eriksson, Mia; Kumlien Georén, Susanna; Winqvist, Ola; Cardell, Lars-Olaf
Abstract Background Allergen-specific immunotherapy represents the only disease-modifying treatment for allergic diseases. We and others have previously demonstrated that intralymphatic immunotherapy (ILIT), a less time-consuming alternative to conventional subcutaneous immunotherapy (SCIT), is safe and effective. However, this has recently been disputed. The aim of this study was therefore to expand our previous trial, further assessing the safety and efficacy of ILIT. Methods Thirty-six patients with pollen-induced rhinoconjunctivitis were randomised to receive three intralymphatic inguinal injections of active allergen (1000 SQ-U birch- or grass-pollen) or placebo. Clinical effects, safety and circulating immunological markers were assessed before, 4 weeks after treatment and at the end of the consecutive pollen season. Results No moderate or severe reactions were recorded following ILIT. Patients receiving active ILIT experienced a significant improvement in self-recorded seasonal allergic symptoms, as compared to placebo (p = 0.05). In a subgroup of these patients ("improved"), a reduction in nasal symptoms following nasal allergen provocation was also demonstrated. No changes in total IgE or IgG4 were found. However, the affinity of allergen specific IgG4 following active treatment was significantly increased, as compared to non-improved patients (p = 0.04). This could be correlated with clinical improvement, on an individual level. Conclusions This double-blinded placebo-controlled study confirms that ILIT is a safe and effective treatment for pollen-induced rhinoconjunctivitis, markedly reducing seasonal allergic symptoms. Trial registration EudraCT:2009-016815-39